Melancholia before the twentieth century: fear and sorrow or partial insanity? - Telles-Correia, Diogo; Marques, João Gama (Frontiers in Psychology, 2015)
Throughout the history of psychopathology, several meanings have been assigned to the term melancholia. The main ones were related to affective disorders (fear and sadness) and abnormal beliefs. At the time of Hippocrates melancholia was regarded mainly in its affective component. Since that time, and until the eighteenth century, authors and opinions have been divided, with both aspects (affective disorders and abnormal beliefs), being valued. Finally, in the eighteenth to nineteenth centuries, with Pinel at its peak, melancholia becomes exclusively a synonym of abnormal beliefs. At the turn of the nineteenth to the twentieth century, the affective component returns as the main aspect characterizing melancholia.